The business of business is the common good - Bergeling, Emma (2021)
New economic theories that seek compatibility with human needs and our planet’s finite resources are emerging within different academic disciplines. For one, there is a growing body of literature considering alternatives to economic growth as potential solutions to the ongoing sustainability crises. Furthermore, a highly relevant question is what the role of businesses, as key economic institutions, is in the transition to a sustainable society. One possible answer to that question is that business in a post-growth future is not-for-profit. The aim of this study is to examine the conditions for not-for-profit businesses in Sweden today, both in terms of their day-to-day operations and their work with sustainability. Three research questions are investigated: one considering the financial, legal and social structures surrounding not-for-profit business, one connecting the absence of a profit distribution motive and sustainability, and lastly, one gazing forward at what structural changes are perceived as important for facilitating a relative increase of not-for-profit business in Sweden. Taking a theoretical stance in structuration theory, institutional economics, theories of sustainable business, and the Not-for-profit framework, the research questions were answered by conducting six semi-structured interviews with representatives from not-for-profit businesses in Sweden. Additionally, a pre-study containing document analysis was conducted. The study concludes that there are constraining financial, legal, and social structures surrounding not-for-profit businesses consisting of for instance the exclusion from investment-willing private capital following the nondistribution constraint, public procurement being perceived as more adapted for the for-profit logic, and a skepticism towards not-for-profit business from banks and for-profit actors in some markets. On the other hand, there are simultaneously enabling structures exemplified by feasible alternative forms of funding, well-adapted association forms, and a positive attitude towards not-for-profit businesses from the public sector, politicians on all sides of the political spectrum as well as the general public. Furthermore, the study concludes that the absence of a profit distribution motive does not automatically entail that not-for-profit businesses are sustainable, but the results indicate that not-for-profit businesses have superior prerequisites to prioritize sustainability compared to for-profit forms of business. Finally, the study concludes that structural changes that are perceived as important for facilitating a relative increase of not-for-profit businesses includes adapting the rules surrounding public procurement, more actors such as unions getting involved, and a value shift away from prioritizing individual gain towards prioritizing gains for the common good.